Activation energy and dual stratification effects for Walter-B fluid flow in view of Cattaneo-Christov double diffusionon. Issue 6 (June 2019) - Ijaz, Misbah; Ayub, Muhammad
Abstract: The purpose of the present article is to explore the novel aspects of activation energy in nonlinearly convective flow of Walter-B nanofluid in view of Cattaneo-Christov double diffusion model over a permeable stretched sheet. Generalized forms of Fourier's and Fick's law are utilized through Cattaneo-Christov double diffusion. Walter-B nanomaterial model is used that describes the significant slip mechanism namely Brownian and thermophoresis diffusions. Double stratification, heat generation/absorption and chemical reaction are considered. Modified Arrhenius formula for activation energy is implemented. The acquired nonlinear system is cracked through homotopic analysis method. Effects of emanating variables are examined through graphs and tables. It is evident that temperature distribution and thermal boundary layer thickness is monotonically dwindling function of thermal stratification parameter ( P 1 ), thermal relaxation time ( δ 2 ) and upsurge for the thermophoresis parameter ( N t ), heat generation/absorption parameter (B₁), Brownian motion parameter ( N b ) . Nanoparticle concentration is directly comparable to the activation energy of reaction and impact of thermal relaxation time is qualitatively opposite to that of thermophoretic force.